Effect of soil type and vermicompost applications on tomato growth - Marc A. Zucco; S. Alan Walters; She-Kong Chong; Brian P. Klubek; Joseph G. Masabni (International Journal of Recycling of Organic Waste in Agriculture)
Background Vermicomposts (VC) improve plant growth and development beyond that normally observed from just soil nutrient transformation and availability. These increases in plant productivity have been attributed to improved soil structure and soil microbial populations that have higher levels of activity and greater production of biological metabolites, such as plant growth regulators. Although there have been many studies on the benefits of VC as a fertilizer source, little research has focused on the effects and/or interactions of soil type and VC application rates on vegetable crop productivity. This paper identifies optimum application rate(s) of VC on tomato growth responses for three different textural classes of soils (loamy sand, silt loam, and silty clay). Results Soils with high VC rates (0.4 and 0.8 g/g) produced taller plants with more leaf and flower numbers, higher leaf chlorophyll content, greater plant biomass, and more total leaf area compared to soils with low VC rates (0.05, 0.1, and 0.2 g/g). Tomato growth increases were also observed at the low VC soil amendment rates compared to the nontreated control. Tomatoes grown in the sandy soil amended with VC generally had the greatest growth responses (plant height, leaf and flower number, and leaf chlorophyll content) compared to the clay or silt loam soils, with the silt loam soil generally providing the least response. Conclusions This research indicated that VC is a suitable alternative fertilizer for tomato, with approximately 0.5â0.6 g/g VC added to soil resulting in optimal tomato plant growth. Moreover, this rate provided tomato growth results similar to the standard inorganic fertility program. The sandy soil with VC amendments generally increased tomato plant growth parameters the most compared to the clay and loam soils, with the loam soil generally providing the least.